Menuju Etika Pendidikan Kesetaraan: Membendung Bias Gender, Mencari Perspektif Humanis - Fawaid, Achmad (Sunan Kalijaga State Islamic University & The Asia Foundation, 2008)
Since last decades gender issue has been a debatable issue in Indonesia, particularly in the field of education. Men generally have access to all stages or levels of education, while women are mostly left behind. Gender equality has been declared nowadays. Women, however, are still discriminated in the field of education. This article offers some important alternatives to solve the problem of gender inequality in education. One of important strategies to deal with the problem is developing an inclusive educational system. This model of education includes six steps: first, revising the language and content of text books which have gender bias; second, encouraging female students to express their cultural differences; third, giving opportunity to female students to be able to access to and participate in all programs and departments in every educational stages, especially the programs that generally are dominated by male students, by developing a new student recruitment system that considers gender balance; fourth, integrating gender equality paradigm in every subject matter and increasing the gender awareness of both teachers and students; fifth, developing extra programs periodically and giving the women an opportunity to be the leader of the program; sixth, making gender balance between the number of male and female teachers and giving them same access and participation in the process of decision making. The strategy, nevertheless, is not enough merely by transforming the educational system and program. The paradigm, more over, has also to be changed. Thus, the writer proposes what so call humanity educational paradigm; the educational system which not only rejects gender inequality, but also makes an effort to eliminate all kinds of humanity based,discrimination and exploitation. The strategy focuses primarily on the empowerment of students. It includes three important parts: power-to, power-with, and power within. By employing this strategy, education will become the most effective medium to eradicate all gender inequality problems and, at the same time, create equality for both women and men in education.